The Implementation of Analog-to-Digital Records Management in Government Institutions to Support the Adoption of an Electronic-Based Government System (A Study at the Office of the Trade Order Supervision Center (BPTN) Surabaya, Ministry of Trade of the Republic of Indonesia) - Aribianto; Nanik Kustiningsih; Sundjoto (Jurnal Ragam Pengabdian, 2026)
This study examines the implementation of the transition from analog to digital records management in a government institution as a strategic effort to support the adoption of an Electronic-Based Government System (SPBE). The research was conducted at the Office of the Trade Order Supervision Center (Balai Pengawasan Tertib Niaga/BPTN) Surabaya, Ministry of Trade of the Republic of Indonesia. A descriptive qualitative approach was employed, with data collected through observation, documentation, and a review of relevant literature. Data analysis involved identifying archival management problems, assessing priority issues using the APKL (Actual, Problematic, Feasible, and Appropriate) method, and formulating strategies through SWOT analysis. The findings reveal that archival management at BPTN Surabaya faced several challenges, including unstructured storage systems, difficulties in document retrieval, limited archival space, and the absence of standardized operating procedures. The study demonstrates that the development of integrated Standard Operating Procedures (SOPs) supported by a database-based digital archival system can significantly improve storage efficiency, accelerate document retrieval, and enhance archival security and sustainability. This research concludes that comprehensive digital records management is not merely a technical solution but a fundamental component of effective, accountable, and sustainable archival governance in supporting government supervision functions and SPBE implementation.